FORMATION OF A UNIFIED INFORMATION MODEL OF DATA REPRESENTATION IN INTELLIGENT INFORMATION ENERGY SYSTEMS - Murodjon Sultanov (Zeta Repository, 2023)
The article carried out a systematic analysis of the functioning of data representation structures in existing energy systems. Based on the results of system analysis, problems and shortcomings of data representation structures in energy information systems were identified, for the elimination of which the use of an intelligent information energy system was proposed. Using the methods of system analysis and the methodology for forming a common information model, a block diagram of information support and a generalized information model of intelligent information energy systems have also been developed. To solve the problems of functioning and development of a unified energy system, an adequate information model has been developed, which is built on the basis of a multidimensional, hierarchical information system consisting of subsystems united by many functional links. It is these connections that make it possible to assess the functional state of subsystems and the system as a whole. In this paper, a new integration mechanism for organizing information interaction of heterogeneous information systems of a single energy system is considered.